Relevansi Teori Akuntansi dan Teori Agensi dalam Praktik Akuntansi di Era Digital: Tinjauan Konseptual dalam Konteks Artificial Intelligence, Machine Learning, dan Internet of Things - Yolanda Noviasari Maramis; Putri Siregar; Iskandar Muda (Yayasan Haiah Nusratul Islam, 2026)
The development of digital technologies has significantly transformed accounting practices, particularly through the use of Artificial Intelligence (AI), Machine Learning (ML), and the Internet of Things (IoT). This transformation raises important questions regarding the relevance of classical accounting theory and agency theory in modern accounting environments. This study aims to evaluate whether both theories remain relevant, undergo adjustment, or face new challenges in digital accounting practices, and to examine how technological developments affect the principles of accountability, transparency, and reliability in financial reporting. This research uses a qualitative descriptive approach with a conceptual analysis based on Donleavy’s (2018) framework in Foundations of Accounting Theory: Theoretical Logic and Professional Ethics and ten international journal articles published in 2025. The findings show that accounting theory and agency theory remain relevant but experience adjustments in explaining the role of technology. At the same time, digital technologies introduce challenges such as algorithmic opacity, data bias, and unclear accountability. Overall, both theories remain essential as conceptual foundations in guiding digital accounting practices.